(untitled) (Journal of the College of Basic Education, 2023)
This work presents a study of radioactivity levels in the soil of LAMA (Active Metallurgy Testing Laboratory) facility after remediation activities. For this purpose, twenty two samples were gathered and analyzed by gamma spectroscopy to quantify radioactivity concentrations of radionuclides using a high-purity germanium detector and spectroscopy system. The absorbed dose rate in air (ADRA) and the annual effective dose (AED) were calculated for the radionuclides according to the guidelines of (UNSCEAR 2000). External hazard index (Hex) for assessment of the radiation hazard of this facility performs according to (Beretka and Mathew) which is below unity. The results obtained were found to be within the allowable limit of 1mSv per year for public exposure recommended.